1990
DOI: 10.3109/02713689009044521
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of alpha crystallin binding to the lens membrane

Abstract: The A1, A2, B1, and B2 species of bovine alpha crystallin have been purified and renatured to form high molecular weight aggregates comprised of only one species, and the aggregated forms of each of these species have been tested for their ability to bind to lens membrane in vitro. The aggregated forms of alpha-A1 and alpha-A2 bound to membrane in a saturable manner while those of alpha-B1 and alpha-B2 bound in much lower amounts, in a manner inconsistent with saturable binding. Together, these results demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 13 publications
1
18
1
Order By: Relevance
“…2). These observations are in contrast to previous reports that suggested that ␣A-crystallin but not ␣B-crystallin was the only subunit involved with membrane association (20,23). Our results also show that this interaction is sensitive to time and temperature, FIG.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…2). These observations are in contrast to previous reports that suggested that ␣A-crystallin but not ␣B-crystallin was the only subunit involved with membrane association (20,23). Our results also show that this interaction is sensitive to time and temperature, FIG.…”
Section: Discussioncontrasting
confidence: 57%
“…In addition, saturable binding to protein-free phospholipid vesicles has been observed, but the measured capacity is reduced dramatically upon incorporation of cholesterol (31)(32)(33). Finally, it has been postulated that ␣B-crystallin is largely unable to bind membranes in the absence of ␣A-crystallin (20,23).…”
mentioning
confidence: 93%
“…Historically, a fraction of ␣-crystallin (both ␣A and ␣B) has been reported to be membrane-associated in the normal adult transparent lens. These observations about the association of ␣-crystallins with the membranes were first made about four decades ago (32)(33)(34)(35). We therefore examined ␣A status first in the lens epithelial explants in culture and then in the early developing lens.…”
Section: Discussionmentioning
confidence: 99%
“…It had been thought to be a lens specific, structural protein until a few years ago. Identification of this protein in several non-lenticular tissues such as heart, muscle and kidney [14] suggests that it might have a role to play in other functions. It is structurally related to small heat-shock proteins (Hsps), behaves in several ways like Hsps [5][6][7][8] and its expression can be induced by thermal [5] and osmotic stress [9].…”
Section: Introductionmentioning
confidence: 99%
“…It is structurally related to small heat-shock proteins (Hsps), behaves in several ways like Hsps [5][6][7][8] and its expression can be induced by thermal [5] and osmotic stress [9]. Like some Hsps [1(~12] it is known to interact with membranes [13,14], cytoskeletal elements [15,16], and to modulate the intermediate filament assembly [17]. Mixed assemblies of ~B and some Hsps have been observed both in vivo [18,19] and in vitro [8].…”
Section: Introductionmentioning
confidence: 99%